Outcome analysis in patients with multi vessel coronary artery disease and left ventricular ejection fraction after percutaneous coronary intervention: single center experience - Singh, Abhimanyu; Banerjee, Tanmay; Kumar, Dilip (International Journal of Research in Medical Sciences, 2020)
Background: The present study evaluated the changes in baseline left ventricular function and clinical symptoms in multi-vessel coronary artery disease patients after multi-vessel percutaneous coronary intervention. Methods: This was a prospective, observational study conducted at Medical Super-speciality Hospital, Kolkata, India, between August 2017 and August 2019. The study included 48 patients who were diagnosed with ≥2 coronary artery stenosis of ≥50% in native coronary arteries with left ventricular ejection fraction (LVEF) <40%. Echocardiography was performed before and after 3 months of the procedure to observe LVEF. Canadian Cardiovascular Society (CCS) score was calculated before and after 3 months after PCI. Results: Mean age of the patients was 61.89±9.96 years and 89.6% patients were male. Mean LVEF before and after angioplasty was 34.9±4.95% and 42.06±8.78%, respectively (p=0.001). CCS score before and after angioplasty was 2.89 and 1.83, respectively (p=0.001). Conclusions: The results displayed significant improvement in clinical symptoms as well as LVEF after PCI in patients with multi-vessel disease with LVEF <40%. These results will be helpful to conduct larger randomized trials with long term follow-up in order to prove the safety and effectiveness of PCI in such patients over coronary artery bypass grafting.